Effects of sustained silent reading on elementary students’ L1, L2, and L3 reading skills - Padilla, Portia P. (Alipato : a Journal of Basic Education, 2021)
Accessed online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/8579